Reduction in the Level of Plasma Mitochondrial DNA in Human Diving, Followed by an Increase in the Event of an Accident - Blatteau, Jean-Eric; Gaillard, Sandrine; De Maistre, Sébastien; Richard, Simone; Louges, Pierre; Gempp, Emmanuel; Druelles, Arnaud; Lehot, Henri; Morin, Jean; Castagna, Olivier; Abraini, Jacques H.; Risso, Jean-Jacques; et al. (Frontiers in Physiology, 2018)
Circulating mitochondrial DNA (mtDNA) is receiving increasing attention as a danger-associated molecular pattern in conditions such as autoimmunity or trauma. In the context of decompression sickness (DCS), the course of which is sometimes erratic, we hypothesize that mtDNA plays a not insignificant role particularly in neurological type accidents. This study is based on the comparison of circulating mitochondrial DNA (mtDNA) levels in humans presenting with various types of diving accidents, and punctured upon their admission at the hyperbaric facility. 114 volunteers took part in the study. According to the clinical criteria there were 12 Cerebro DCS, 57 Medullary DCS, 15 Vestibular DCS, 8 Ctrl + (accident-free divers) and 22 Ctrl - (non-divers). This work demonstrates that accident-free divers have less mtDNA than non-divers, which leads to the assumption that hyperbaric exposure degrades the mtDNA. mtDNA levels are on average greater in divers with DCS compared with accident-free divers. On another hand, the amount of double strand DNA (dsDNA) is neither significantly different between controls, nor between the different DCS types. Initially the increase in circulating oligonucleotides was attributed to the destruction of cells by bubble abrasion following necrotic phenomena. If there really is a significant difference between the Medullary DCS and the Ctrl-, this difference is not significant between these same DCS and the Ctrl +. This refutes the idea of massive degassing and suggests the need for new research in order to verify that oxidative stress could be a key element without necessarily being sufficient for the occurrence of a neurological type of accident.